2007
DOI: 10.1002/hep.22177
|View full text |Cite
|
Sign up to set email alerts
|

Acute liver failure: Summary of a workshop

Abstract: Acute liver failure (ALF) is a rare but challenging clinical syndrome with multiple causes; a specific etiology cannot be identified in 15% of adult and 50% of pediatric cases. The course of ALF is variable and the mortality rate is high. Liver transplantation is the only therapy of proven benefit, but the rapidity of progression and the variable course of ALF limit its use. Currently in the United States, spontaneous survival occurs in approximately 45%, liver transplantation in 25%, and death without transpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
503
2
25

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 638 publications
(553 citation statements)
references
References 168 publications
(184 reference statements)
13
503
2
25
Order By: Relevance
“…High doses of NAC are recommended in such patients and should be started within 48 h of ingestion. 5 Pregnancy and acute liver failure: There is increased risk of maternal and fetal complications in pregnant patients with ALF. 81 The principles of management of abortions, preterm labor, premature rupture of membranes and still birth remain unchanged.…”
Section: Molecular Adsorbent Recirculating System (Mars)mentioning
confidence: 99%
See 1 more Smart Citation
“…High doses of NAC are recommended in such patients and should be started within 48 h of ingestion. 5 Pregnancy and acute liver failure: There is increased risk of maternal and fetal complications in pregnant patients with ALF. 81 The principles of management of abortions, preterm labor, premature rupture of membranes and still birth remain unchanged.…”
Section: Molecular Adsorbent Recirculating System (Mars)mentioning
confidence: 99%
“…1 However, the interval between onset of acute hepatic injury (jaundice) and onset of liver failure (encephalopathy with or without coagulopathy) in such patients (icterus-encephalopathy interval; IEI) has been described to be between 4 weeks (Indian definition) [2][3][4] to 24 weeks (AASLD-ALF study group). 5 Further, due to the diverse natural course, ALF has been sub-classified as hyperacute (IEI # 7 day), acute (IEI # 4 weeks) and sub-acute ALF (IEI $ 5 week to #12 weeks) by British authors. 6 Despite these differences in definitions, the central and most important clinical event in ALF is occurrence of hepatic encephalopathy (HE) and cerebral edema which is responsible for most of the fatalities in this serious clinical syndrome.…”
mentioning
confidence: 99%
“…In our study, animals had the ALT levels peak at day 1, started to decrease at day 2 and had returned to basal values at day 3. Lee et al (12) , analyzing 1,147 cases of APAP-induced ALF in humans demonstrated that ALT levels are very high (2,138 to 6,731). However, in APAP-induced hepatotoxicity in rats ALT levels are lower in comparison with humans, around of 256.5 ± 11.2 (23) .…”
Section: Discussionmentioning
confidence: 99%
“…Acetaminophen (APAP) toxicity is the leading cause of ALF in the United States and United Kingdom, accounting for 46% and 70% of cases, respec-tively (12,24) . The mechanism of liver toxicity is well established.…”
Section: Introductionmentioning
confidence: 99%
“…Despite several advances in the clinical management of patients with acute liver failure (ALF), this condition remains extremely serious and results in high mortality rates. Viral hepatitis and drug-induced hepatotoxicity (in particular acetaminophen overdose) are the most frequent causes of ALF, although their relative incidence varies markedly in different parts of the world 1 . The difficulties inherent to the management of patients with ALF can be explained in part by the serious systemic and neurological complications of ALF, which include hypoglycemia, renal failure, coagulopathy, sepsis, multiorgan failure, intracranial hypertension, and hepatic encephalopathy 2 .…”
Section: Introductionmentioning
confidence: 99%